The analysis of quaternary cave sediments and its bearing upon palaeolithic archaeology, with special reference to selected sites from western Britain - Collcutt, SN (1984)
The present thesis constitutes a reassessment of quaternary cave sediment analysis and its relationships to palaeolithic archaeology. Traditionally, archaeological cave sediments have been interpreted in climatic terms, the arguments usually being based upon compositional and textural parameters measured in the laboratory using a fixed batch of analytical techniques. The author demonstrates that this approach is unsound, both because of the simplistic interpretative framework employed and because, even when highly sophisticated techniques are used, it is often difficult to isolate climatic controls, factors which are only a small part of the lithogenetic process. The author has concentrated upon contextual matters, giving priority to the deduction of sedimentary environments through actualistic principles. Great importance is attached to structure, geometry and facies, features which are best observed on site. Thus, the author addresses the primary problem of how a sediment formed. This problem is fundamental to archaeology and all other object-oriented disciplines since, without a solution, one cannot assess the significance of assemblages with any degree of confidence. Furthermore, any climatic information which is indeed available can only be extracted once a firm contextual framework has been established. The thesis has been split into two Parts. The first Part contains a review of sedimentological theory as applicable to cave deposits. This involve discussion of basic principles (the cave environment, properties of sediments, fieldwork, boundary features, stratigraphy, quantification, analytical techniques), process groupings (mechanisms and effects of ice formation, mass movement, water movement, wind, alteration, chemical precipitation) and more synthetic topics (biological material, provenance, palaeogeography, diagenesis, correlation, dating methods, synthesis of results, archaeological concepts). The second Part comprises a discussion of various British cave sites (South Devon, Mendip, Gower, North Wales), each section being presented, not as a site report, but as an illustration of some of the theoretical points raised in the first Part.